Who Are You?. Issue 6 (26th December 2018) - Gilbert, Susan
Abstract: At a time when our views on practically everything are polarized, there's one thing that growing numbers of us agree on: we want genetic information about ourselves. About 15 million people have taken a direct‐to‐consumer genetic test, up from 4 million two years ago. Millions more are likely to give these tests as holiday gifts. Many people consider genetic findings deeply meaningful to their understanding of who they are. This information is a gift, but it is also a weight—a paradox that was the theme of a conference organized by my colleagues Erik Parens and Joel Michael Reynolds in October 2018. Genomic knowledge is a gift when, for example, it connects us with relatives whom we're glad to meet. But it is a weight when it pigeonholes us into categories that suggest racial differences and possibly stereotypes .